SMEs’s potentials of Research and Development and the European Union Prospective. A Literature Review - Loreta Isaraj (Academicus, 2021)
SME-s role in the economic development and economic structure is changing drastically, as it is gaining new dimensions the role they have as social agents. This becomes particularly present in the paradigm shift of the EU funding schema and priorities, for member and candidate states, indicating that from catalysts of development they are now considered as important and active agents of Innovation by their R&D potential. The article provides a comprehensive literature review on different aspects of R&D processes in SMEs under the support of the funding programs of European Union collected from the reputed publications. The purpose is to provide an outline on the structure and dynamics of R&D in SMEs to highlight its role in the performance of these businesses in particular and in national and regional economies at the macro level. This paper aims to contribute to current discussions within the field of innovation by further exploring how EU R&D funding policies work in practice.